Benzene control from waste gas streams with a sponge-medium based rotating biological contactor. (April 2016) - Padhi, Susant Kumar; Gokhale, Sharad
Abstract: Rotating biological contactors (RBCs) are low-cost, efficient and an eco-friendly volatile organics control technique. In this study, a state-of-art disk-based RBC has been modified to a drum-based with sponge supporting medium and its performance at different inlet loading rates (ILR) of gaseous benzene, and its effect on elimination capacity (EC) and removal efficiency (RE) have been investigated. The results showed that the RE remained over 90% up to the ILR of about 8 g m −3  h −1, and decreased to about 80% with the further increase in ILR. The EC reached maximum to about 45 g m −3  h −1  at a benzene load of about 69 g m −3  h −1 . The EC of benzene increased with the increase in loading rate, but the RE showed an opposite trend. The production of carbon dioxide, which determines the degree of pollutant degradability, also increased with the increase in EC. Along with benzene the nutrients (NH3 –N and PO4 –P) from liquid phase also got removed in RBC, which shows its potential application in industries. Furthermore, a potential benzene degrader was tentatively identified as genera Enterobacter . The maximum biodegradation rate (rmax ) and half saturation constant (Ks ) were determined as 21.46 g m −3  h −1 and 1.71 g m −3, respectively. Graphical abstract: Highlights: The proposed RBC removed benzene from waste gas streams up to 95%. The RBC designed with perforated drum and sponge-medium was operated for 138 days. The RBC could treat gaseous benzene and nutrients from liquid simultaneously. The predominant benzene degrader was tentatively identified as Enterobacter sp.